El malestar en la relación médico- paciente - Manitta, Gabriela (Acta Bioethica, 2005)
The possibility to recognize the madness that certain norms generate, such as the one that pretends to transform the medical action into an automaton's operation is stated around the uneasiness in the physician-patient relationship. Physicians may assume a different position if they are willing to keep in themselves the sight of their own ignorance about the inalienable particularity of each sick person, and of the individual history that shelters the symptoms. Because even though we can assert that the patient's rights have been respected, we know nothing about him. In order to recognise his patient's particularity, and for the patient to acknowledge himself in that particularity, the doctor has to face him as if he was facing a mystery.